Peningkatan Pemahaman Kepada Masyarakat Kecamatan Medan Johor Tentang Pengawasan Kerja dan Kinerja Pegawai - Juniarti Juniarti; Batubara, Tomi Widodo (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
The purpose of this community service is to increase understanding to the community of Medan Johor sub-district about work supervision and employee performance. The specific target in this community service is for the people of Medan Johor sub-district to know what work supervision and employee performance are. The materials presented in this community service are: what is work supervision, and employee performance. The connection will affect the improvement of community work in Medan Johor sub-district so that the community gets a solution to work supervision and employee performance. From this community service, the results show that the community of Medan Johor sub-district has known and understood the importance of insight into work supervision and employee performance so as to improve work performance.